Reliability analysis of radiographic methods for determination of posterolateral lumbossacral fusion - Alberto Ofenhejm Gotfryd; Felipe de Moraes Pomar; Nicola Jorge Carneiro Neto; Fernando José Franzin; Luciano Miller Reis Rodrigues; Patricia Rios Poletto (Einstein (São Paulo))
Objective To analyze intra and interobserver agreement of two radiographic methods for evaluation of posterolateral lumbar arthrodesis.Methods Twenty patients undergoing instrumented posterolateral fusion were evaluated by anteroposterior and dynamic lateral radiographs in maximal flexion and extension. The images were evaluated initially by 6 orthopedic surgeons, and after 8 weeks, reassessed by 4 of them, totaling 400 radiographic measurements. Intra and interobserver reliability were analyzed using the Kappa coefficient and Landis and Koch criteria.Results Intra and interobserver agreement regarding anteroposterior radiographs were, respectively, 76 and 63%. On lateral views, these values were 78 and 84%, respectively. However, the Kappa analysis showed poor intra and interobserver agreement in most cases, regardless of the radiographic method used.Conclusion There was poor intra and interobserver agreement in the evaluation of lumbosacral fusion by plain film in anteroposterior and dynamic lateral views, with no statistical superiority between the methods.